Kepemilikan Asing, Kinerja Perusahaan, dan Volatilitas Return pada Perusahaan Non-Keuangan BEI Tahun 2020–2022 - Eka Fitri Mulyani (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
This study examines the effect of foreign ownership on firm performance and return volatility, as well as the moderating role of corporate governance in non-financial companies listed on the Indonesia Stock Exchange (IDX) during the COVID-19 pandemic period of 2020–2022. The COVID-19 pandemic created significant economic uncertainty, disrupted business activities, and increased capital market volatility, making effective corporate governance and foreign investment increasingly important in maintaining corporate performance and market stability. This study employs a quantitative explanatory approach using panel data regression and Moderated Regression Analysis (MRA). The sample consists of non-financial companies selected through purposive sampling based on data availability and research criteria. Foreign ownership is measured by the percentage of shares held by foreign investors, while firm performance is proxied by Return on Assets (ROA), Return on Equity (ROE), and Tobin’s Q. Return volatility is measured using the standard deviation of ROA, ROE, and stock returns, whereas corporate governance is proxied by board size. The findings indicate that foreign ownership significantly affects firm performance and return volatility. Although foreign ownership shows a negative relationship with accounting-based performance measures (ROA and ROE), it positively influences market-based performance (Tobin’s Q) and reduces return volatility. Furthermore, corporate governance strengthens the relationship between foreign ownership and both firm performance and return volatility, suggesting that effective governance enhances the benefits of foreign ownership during periods of economic uncertainty. These findings contribute to the literature on foreign ownership, corporate governance, and corporate resilience, while providing practical implications for managers, investors, and policymakers in strengthening corporate governance and attracting foreign investment during periods of economic crisis.